Patient empowerment for lifestyle changes in metabolic-bariatric surgery: a German nationwide survey - Finze, Alida; Reißfelder, Christoph; Blank, Susanne; Otto, Mirko; Stier, Christine; Meier, Rafael; Schreiter, Johanna; Nicolli, Anastasia; Quenstedt, Tim; Tigiser, Elias; Yang, Cui (Obesity surgery, 2025)
Background Compliance with postoperative follow-up, physical activity, and nutrition is a known problem in patients receiving metabolic-bariatric surgery (MBS). This issue needs to be tackled not only through intervention studies. Patients’ personal preferences and concerns need to be the center of a successful improvement of pre-and postoperative care in MBS. Methods A total of 323 participants from support groups all over the country were interviewed via an online survey concerning physical activity, use of media and health-related phone applications, and eating behavior. In addition, 14 open patient interviews were pursued before or after MBS regarding physical activity, eating behavior, and media use. Results Of subjects, 64.7% preferred small training groups of 6-10 people. The most popular types of sports were aqua sports, followed by walking and bicycle sports. One-third of the participants stated not enjoying the gym at all. In the open patient interviews, the main reason for this was fear of stigmatization. Sixty-three percent of patients stated a willingness to participate in a sports program designed specifically for MBS patients. Conclusions Overall willingness towards an increase in physical activity after MBS is present. However, stigma and pain during sports or the inability to perform certain sports seem to be the main issue keeping patients away from physical activity. We suggest clinical trials towards training protocols in small groups of 6-10 people, aqua, walking, or biking sports, and specialized training protocols for MBS patients.
Online veröffentlicht: 23. Juni 2025
Gesehen am 25.09.2025